On the atom bond connectivity index of certain trees and unicyclic graphs - Mohammed, Mohanad Ali; Mohd Atan, Kamel Ariffin; Khalaf, Abdul Jalil Manshad; Hasni @ Abdullah, Roslan (IEEE, 2015)
The atom-bond connectivity (ABC) index is one of the recently most investigated degree based molecular structure descriptors that have applications in chemistry. For a graph G, the ABC index is defined as ABC(G) = Σuvϵ √(du + dv-2) /du/dv, where du denotes the degree of a vertex u in G. In this paper, we obtain the general formula of the ABC index for certain trees and unicyclic graphs with their representing by Alkanes and Cycloalkanes.